Mengembangkan Minat Wirausaha Anak Muda : Kunci Sukses Entrepreneurship dan Life Skills - Sutarman Laia; Emilia Wori Hana; Putri Sory; Yosia Bello (Journal of Student Research, 2025)
Entrepreneurship is not something that can only be achieved by individuals who have certain talents, on the contrary, by taking business risks in creating new opportunities, one can develop an entrepreneurial spirit. However, entrepreneurship must be accompanied by interest. Interest is a strong drive within a person to do something. Based on this study analyzing the influence of entrepreneurial skills on the success of a business, the type of descriptive research carried out through data collection in the field, the method used in this study is an explanatory survey. This article emphasizes that fostering entrepreneurial interest is not only beneficial for individual economic success, but also contributes to economic growth and innovation in society. The importance of encouraging entrepreneurial interest among young people as a foundation for building success in the world of entrepreneurship. By having a strong interest in entrepreneurship, young people can develop important life skills such as creativity, perseverance, risk management, and problem solving.